C60 / CNT composite photocatalytic material as well as preparation method and application thereof

By combining C60 with carbon nanotubes, C60/CNT composite photocatalytic material is formed, the problem of low efficiency of single carbon nanotube photocatalytic material is solved, efficient degradation of lomefloxacin hydrochloride is achieved, and significant photocatalytic activity is shown under LED light.

CN119793433APending Publication Date: 2025-04-11HUBEI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411991673.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing single carbon nanotube photocatalytic materials have low photocatalytic efficiency and are difficult to effectively remove lomefloxacin hydrochloride and its degradation problems in the environment.

Method used

A C60/CNT composite photocatalytic material is developed to enhance the specific surface area and photocatalytic activity of the material by combining C60 with carbon nanotubes, which are coated on the surface of the carbon nanotube or doped in the gaps.

Benefits of technology

The photocatalytic degradation efficiency was significantly improved. The degradation efficiency of C60/CNT composite materials on lomefloxacin hydrochloride was up to 87%, and showed efficient photocatalytic activity under LED lighting conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793433A_ABST
    Figure CN119793433A_ABST
Patent Text Reader

Abstract

The invention provides a C60 / CNT composite photocatalytic material as well as a preparation method and application thereof, and belongs to the technical field of photocatalytic materials. The C60 / CNT composite photocatalytic material is prepared from C60 and a carbon nanotube, the mass ratio of the C60 to the carbon nano tube is 0.002 to 0.1; wherein the C60 is coated on the surface of the carbon nano tube or doped in gaps of the carbon nano tube. The preparation method of the composite photocatalytic material is simple and rapid, and the obtained C60 / CNT composite photocatalytic material has wide application prospects in the fields of adsorption and photocatalysis. In the field of lomefloxacin hydrochloride adsorption, the highest degradation efficiency of the C60 / CNT composite material with the mC60 / mCNT ratio of 0.2% reaches 87%; in the field of photocatalytic degradation of lomefloxacin hydrochloride, mC60 / mCNT is 5% of the C60 / CNT composite material, and the photocatalytic degradation efficiency is highest.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a C 60 / CNT composite photocatalytic material and its preparation method and application. Background Art

[0002] Lomefloxacin hydrochloride is a widely used quinolone antibiotic, commonly used to treat bacterial infections. However, its drug resistance and side effects cannot be ignored, so the rational treatment of antibiotic pharmaceutical wastewater is a relatively important link. In order to reduce its potential threat to the environment, especially its accumulation in water bodies, it is particularly important to study how to effectively remove lomefloxacin hydrochloride and its degradation in the environment.

[0003] At present, photocatalytic technology has shown great potential in the treatment of antibiotic pharmaceutical wastewater. Photocatalytic technology uses semiconductor materials to produce strong oxidizing free radicals under light, thereby degrading antibiotic molecules. Compared with traditional photocatalysts such as TiO2, which mainly work under ultraviolet light, the development of new photocatalysts not only overcomes the energy limitation of the ultraviolet light band, but also has a wider light response range, broadening the application scope of photocatalytic technology. However, the current mainstream photocatalysts are mostly composed of metal oxide composites, metals are prone to secondary pollution, and the excitation light of current photocatalysts is mostly xenon lamps, which have high energy consumption.

[0004] In recent years, the adsorption performance and photocatalytic activity of carbon nanotubes (CNTs) have attracted widespread attention, mainly because CNTs have good chemical stability and high temperature resistance, and therefore have broad prospects in the adsorption of pollutants in water and photocatalytic oxidation of environmental pollutants. However, the photocatalytic efficiency of single carbon nanotubes is low, so the development of a modified carbon nanotube photocatalytic material is of great significance. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present invention provides a C 60 / CNT composite photocatalytic material and its preparation method and application are aimed at solving the technical problems of low photocatalytic efficiency of existing single carbon nanotube photocatalytic materials and degradation and removal of lomefloxacin hydrochloride.

[0006] In a first aspect, the present invention provides a C 60 / CNT composite photocatalytic materials, including C 60 and carbon nanotubes; C 60 The mass ratio of C to carbon nanotubes is 0.002~0.1; 60 Coated on the surface of carbon nanotubes and / or the C 60 Doped in the gaps between carbon nanotubes.

[0007] Preferably, C 60 The mass ratio to carbon nanotubes is 0.002~0.05.

[0008] In a second aspect, the present invention provides a C 60 The preparation method of CNT composite photocatalytic material comprises the following steps: CNT materials and C 60 The material is placed in a solvent, mixed and then subjected to ultrasonic treatment, followed by centrifugal separation, and the separated product is dried and ground to obtain C 60 / CNT composites.

[0009] Preferably, the solvent includes water and anhydrous ethanol.

[0010] Preferably, the volume ratio of water to anhydrous ethanol is 1:1.

[0011] Preferably, the ultrasonic treatment time is 1 to 2 hours.

[0012] Preferably, the drying temperature is 80-90° C. and the drying time is 5-8 hours.

[0013] In the present invention, grinding until completely loosened is sufficient, and the grinding method includes but is not limited to various mechanical grinding methods such as ball milling and roller milling.

[0014] In a third aspect, the present invention provides a C 60 Application of CNT composite photocatalytic materials in adsorption and degradation of lomefloxacin hydrochloride, 60 The mass ratio of / CNT composite photocatalytic material to lomefloxacin hydrochloride before degradation is 0.8~1.2:1.

[0015] Preferably, C 60 C / CNT composite photocatalytic material 60 The mass ratio to carbon nanotubes is 0.002.

[0016] In a fourth aspect, the present invention provides a C 60 Application of CNT composite photocatalytic materials in photocatalytic degradation of lomefloxacin hydrochloride, 60 The mass ratio of / CNT composite photocatalytic material to lomefloxacin hydrochloride before degradation is 0.8~1.2:1.

[0017] Preferably, C 60 C / CNT composite photocatalytic material 60 The mass ratio of carbon nanotubes is 0.05.

[0018] Preferably, potassium persulfate is added as an auxiliary agent in the photocatalytic degradation of lomefloxacin hydrochloride.

[0019] Preferably, the light source used for photocatalytic degradation of lomefloxacin hydrochloride includes an LED light source.

[0020] The principle of the technical solution of the present invention is as follows: C is introduced into the CNT material. 60 The surface roughness and specific surface area of ​​CNTs are increased, which increases their adsorption effect. In addition, studies have shown that C 60 The work function of CNT is 5.1 eV, which is higher than that of CNT (4.6 eV). Therefore, in the field of photocatalytic degradation of lomefloxacin hydrochloride, under LED illumination, CNT 60 The photogenerated electrons excited by CNTs in the CNT / CNT composite photocatalytic material can be quickly transferred to the 60 , thus significantly improving the separation efficiency of photogenerated carriers. The separated electrons can react with O2 and reduce it to ·O 2- , which can promote the catalytic degradation of lomefloxacin hydrochloride. 60 When the / CNT composite photocatalytic material is photocatalytically degraded together, some of the separated electrons can activate potassium persulfate to generate SO4 - and 1 O2, the system is based on O 2- As the main active substance, supplemented by SO4 - and 1 O2 acts as a secondary active substance, and multiple active substances work synergistically to effectively promote the oxidative degradation of lomefloxacin hydrochloride and significantly improve the photocatalytic degradation efficiency.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a C 60 / CNT composite photocatalytic material, composed of C 60 and carbon nanotubes, C 60 The composite photocatalytic material is coated on the surface of the carbon nanotube or doped in the gap between the carbon nanotubes. The preparation method of the composite photocatalytic material is simple and fast. 60 / CNT composite photocatalytic materials have high specific surface area, high adsorption capacity, visible light response and charge transfer ability, and have broad application prospects in the fields of adsorption and photocatalysis. In the field of adsorption of lomefloxacin hydrochloride, m C60 / m CNT 0.2% C 60 / CNT composite material degradation efficiency reached up to 87%; in the field of photocatalytic degradation of lomefloxacin hydrochloride, m C60 / m CNT 5% C 60 / CNT composite materials have the highest photocatalytic degradation efficiency. In addition, compared with the current mainstream photocatalytic materials that are mostly xenon lamp catalysis, the present invention uses LED lamps for photocatalysis, which is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 For the present invention C 60 , CNT and C prepared in Example 4 60 SEM spectra of / CNT composites; Figure 1 (a) and Figure 1 (d) is the SEM image of CNT. Figure 1 (b) and Figure 1 (e) is C 60 SEM images of Figure 1 (c) and Figure 1 (f) is C 60 SEM images of / CNT composites; Figure 2 For the present invention C 60 , CNT and C prepared in Example 4 60 Transmission electron microscope spectra of / CNT composites; Figure 2 (a) is C 60 TEM image of Figure 2 (b) is the TEM image of CNT. Figure 2 (c) and Figure 2 (d) is C 60 TEM image of / CNT composites; Figure 3 The present invention is different from C 60 / CNT composite photocatalytic material light absorption characteristics test results spectrum; Figure 3 (a) is the UV-Vis diffuse reflectance spectrum; Figure 3 (b) CNT and C prepared in Example 4 60 Bandgap diagram of / CNT composites; Figure 4 The present invention is different from C 60 Figure 3. Test results of recombination efficiency of photogenerated carriers of / CNT composite photocatalytic materials. DETAILED DESCRIPTION

[0023] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.

[0024] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0025] 1. Preparation method Example 1 A C 60 The preparation method of CNT composite photocatalytic material comprises the following steps: Weigh 1g of CNT material and 0.002g of C 60 The material was placed in a 50 ml centrifuge tube, 10 ml of water and 10 ml of anhydrous ethanol were added, and the mixture was shaken and then subjected to ultrasonic dispersion for 2 hours. After the ultrasonic dispersion was completed, the separated product was dried at 85 ° C for 6 hours, and then ground into powder using an agate mortar until it was completely loose, thus obtaining m C60 / m CNT 0.2% C 60 / CNT composite material, denoted as CC0.2.

[0026] Example 2 A C 60 The preparation method of CNT composite photocatalytic material comprises the following steps: Weigh 1g of CNT material and 0.005g of C 60 The material was placed in a 50 ml centrifuge tube, 10 ml of water and 10 ml of anhydrous ethanol were added, and the mixture was shaken and then subjected to ultrasonic dispersion for 2 hours. After the ultrasonic dispersion was completed, the separated product was dried at 85 ° C for 6 hours, and then ground into powder using an agate mortar until it was completely loose, thus obtaining m C60 / m CNT 0.5% C 60 / CNT composite material, denoted as CC0.5.

[0027] Example 3 A C 60 The preparation method of CNT composite photocatalytic material comprises the following steps: Weigh 1g of CNT material, 0.01g of C 60 The material was placed in a 50 ml centrifuge tube, 10 ml of water and 10 ml of anhydrous ethanol were added, and the mixture was shaken and then subjected to ultrasonic dispersion for 2 hours. After the ultrasonic dispersion was completed, the separated product was dried at 85 ° C for 6 hours, and then ground into powder using an agate mortar until it was completely loose, thus obtaining m C60 / m CNT 1% C 60 / CNT composite material, denoted as CC1.

[0028] Example 4 A C 60 The preparation method of CNT composite photocatalytic material comprises the following steps: Weigh 1g of CNT material and 0.05g of C 60The material was placed in a 50 ml centrifuge tube, 10 ml of water and 10 ml of anhydrous ethanol were added, and the mixture was shaken and then subjected to ultrasonic dispersion for 2 hours. After the ultrasonic dispersion was completed, the separated product was dried at 85 ° C for 6 hours, and then ground into powder using an agate mortar until it was completely loose, thus obtaining m C60 / m CNT 5% C 60 / CNT composite material, denoted as CC5.

[0029] The SEM image is as follows: Figure 1 (c) and Figure 1 (f) shows the transmission electron microscope TEM image. Figure 2 (c) and Figure 2 As shown in (d), we can see that part C 60 Coated on the surface of carbon nanotubes, some C 60 Doped in the gaps between carbon nanotubes.

[0030] According to the N2 adsorption-desorption curve, the specific surface area of ​​CC5 composite material is 136.4765 m 2 / g.

[0031] Example 5 A C 60 The preparation method of CNT composite photocatalytic material comprises the following steps: Weigh 1g of CNT material, 0.1g of C 60 The material was placed in a 50 ml centrifuge tube, 10 ml of water and 10 ml of anhydrous ethanol were added, and the mixture was shaken and then subjected to ultrasonic dispersion for 2 hours. After the ultrasonic dispersion was completed, the separated product was dried at 85 ° C for 6 hours, and then ground into powder using an agate mortar until it was completely loose, thus obtaining m C60 / m CNT 10% C 60 / CNT composite material, denoted as CC10.

[0032] Comparative Example 1 A C 60 The preparation method of CNT composite photocatalytic material comprises the following steps: Weigh 1g of CNT material and 0.15g of C 60 The material was placed in a 50 ml centrifuge tube, 10 ml of water and 10 ml of anhydrous ethanol were added, and the mixture was shaken and then subjected to ultrasonic dispersion for 2 hours. After the ultrasonic dispersion was completed, the separated product was dried at 85 ° C for 6 hours, and then ground into powder using an agate mortar until it was completely loose, thus obtaining m C60 / m CNT 15% C 60 / CNT composite material, denoted as CC15.

[0033] Comparative Example 2 A C 60 The preparation method of CNT composite photocatalytic material comprises the following steps: Weigh 1g of CNT material and 0.2g of C 60 The material was placed in a 50 ml centrifuge tube, 10 ml of water and 10 ml of anhydrous ethanol were added, and the mixture was shaken and then subjected to ultrasonic dispersion for 2 hours. After the ultrasonic dispersion was completed, the separated product was dried at 85 ° C for 6 hours, and then ground into powder using an agate mortar until it was completely loose, thus obtaining m C60 / m CNT 20% C 60 / CNT composite material, denoted as CC20.

[0034] Comparative Example 3 This comparative example is pure carbon nanotube CNT material, and its SEM image is as follows Figure 1 (a) and Figure 1 (d) shows the transmission electron microscope TEM image. Figure 2 (b) According to the N2 adsorption-desorption curve, the specific surface area of ​​CNT material is 109.1177 m 2 / g, Comparative Example 4 This comparative example is pure C 60 The material, the SEM image is as follows Figure 1 (b) and Figure 1 (e) shows the transmission electron microscope TEM image. Figure 2 (a) shown.

[0035] 2. Test Method (1) C 60 Test on light absorption characteristics of CNT composite photocatalyst UV-Vis diffuse reflectance spectroscopy was used to test C 60 , CNT and C prepared by the present invention 60 Light absorption characteristics of CNT composite photocatalytic materials.

[0036] (2) C 60 Recombination efficiency test of photogenerated carriers of CNT composite photocatalyst Using photoluminescence spectroscopy to study the recombination efficiency of photogenerated carriers, C 60 , CNT and C prepared by the present invention 60 / CNT composite photocatalytic materials were all measured under 350nm wavelength excitation.

[0037] (3) C 60Test on the adsorption and degradation efficiency of lomefloxacin hydrochloride by CNT composite photocatalytic materials Using CNT and different C 60 The / CNT composite material was used as an adsorbent and added into 100 mL of lomefloxacin hydrochloride (LOMH) solution with an initial concentration of 20 mg / L. The adsorbent dosage was 20 mg / L. Under the conditions of pH 6.5 and reaction temperature of 25 °C, the adsorption of CNT and different CNTs prepared by the present invention was investigated. 60 Effect of CNT / CNT composites on LOMH degradation efficiency.

[0038] The adsorption process was carried out in a 250 mL beaker. To quantify the adsorption, 2.5 mL of the supernatant was collected using a syringe and filtered into a 5 mL centrifuge tube using a water filter. The residual lomefloxacin hydrochloride concentration was measured using an ultraviolet spectrophotometer (wavelength 287 nm), and all experiments were repeated 3 times. The degradation efficiency was calculated as follows: [(C0-C a ) / C0]×100%; where C a represents the lomefloxacin concentration from the beginning of adsorption to time t, and C0 represents the initial concentration.

[0039] (4) C 60 Test on the photocatalytic degradation efficiency of lomefloxacin hydrochloride by CNT composite photocatalytic materials Using C 60 , CNT and different C 60 / CNT composite material was used as a photocatalyst, and the photocatalytic experiment was carried out by degrading LOMH under an LED light equipped with 400nm. The photocatalyst was added to 50mL of LOMH solution with an initial concentration of 20mg / L in a photocatalytic reactor, and the photocatalyst concentration was 0.02g / L. Before irradiation, the suspension was stirred in the dark for 30 minutes to reach adsorption equilibrium. After adsorption equilibrium, the light was turned on to irradiate the solution, and 2.5mL of the solution was taken every 10min and filtered through a needle filter to obtain a clear solution. Then, the absorbance of the solution was measured at 287nm using an ultraviolet spectrophotometer to analyze the solution concentration. The calculation formula for photocatalytic degradation efficiency is: [(C0-C) / C0]×100%; where C represents the solution concentration at the photocatalytic moment and C0 represents the initial concentration.

[0040] III. Analysis of test results of various embodiments and comparative examples (1) C 60 Light absorption characteristics of CNT composite photocatalysts like Figure 3 (a) UV-Vis diffuse reflectance spectrum shows that in the wavelength range of 200nm to 800nm, pure carbon nanotubes (CNTs) exhibit good visible light absorption ability, while C 60The absorption bands of CC1 composite material prepared in Example 3 and CC5 composite material prepared in Example 4 are close to CNT, which indicates that CNT 60 The introduction ratio of CNT is low and no significant element doping effect is produced on CNT. 60 When the introduction ratio of C increases to 10% and 15%, the composite material shows the same 60 Similar absorption characteristics. Compared with other prepared composite materials, the CC5 composite material prepared in Example 4 shows the strongest visible light absorption ability. In order to further confirm the band gap values ​​of CNT and CC5 composite materials, the Kubelka-Munk function was used to draw the Tauc plot, as shown in Figure 3 As shown in (b), the calculated band gap of CNT is 1.37 eV and the band gap of CC5 composite is 1.46 eV, indicating that the band gap of CC5 composite is larger than that of CNT, which further verifies its enhanced visible light absorption ability.

[0041] (2) Recombination efficiency of photogenerated carriers Figure 4 The present invention is different from C 60 The recombination efficiency test results of photogenerated carriers of / CNT composite photocatalytic materials, such as Figure 4 As shown, the CC5 composite material prepared in Example 4 exhibits a peak similar to that of CNT. 60 When the doping ratio increases, the composite material shows a similar C 60 The characteristic peaks of C 60 Generally speaking, lower photoluminescence (PL) intensity indicates lower recombination efficiency of photogenerated electrons and holes, leading to higher photocatalytic activity, in all CNT-containing 60 Among the composite materials, CC5 prepared in Example 4 has the lowest PL intensity, indicating that its photocatalytic activity is the most significant.

[0042] (3) C 60 Adsorption and degradation efficiency of lomefloxacin hydrochloride by CNT composite photocatalytic materials The present invention is different from 60 The adsorption and degradation efficiency of lomefloxacin hydrochloride by the / CNT composite photocatalytic material after 240 minutes of adsorption and degradation is shown in Table 1.

[0043] Table 1

[0044] From the results in Table 1, it can be seen that the CC0.2 composite material prepared in Example 1 has the largest adsorption degradation rate of LOMH, which is 87.1%. This should be due to the fact that the introduction of a small amount of C60 increases the specific surface area and increases the adsorption active sites. When the amount of C60 introduced increases, the degradation rate of LOMH by the CC15 composite material prepared in Comparative Example 1 decreases to 25.28%. This may be because excessive C60 causes CNT pipeline blockage, thereby reducing the specific surface area of ​​the material and causing a decrease in LOMH adsorption efficiency.

[0045] (4) C 60 Photocatalytic degradation efficiency of lomefloxacin hydrochloride by CNT composite photocatalytic materials The present invention is different from 60 The photocatalytic degradation efficiency of the / CNT composite photocatalytic material when photocatalytically degrading LOMH for 60 minutes under LED light irradiation is shown in Table 2.

[0046] Table 2

[0047] From the results in Table 2, we can see that after the introduction of C 60 The modified composite catalyst is generally improved compared with pure CNT. 60 When the doping ratio of CC5 is 1%, the degradation rate of the composite catalyst and pure CNT is slightly different. When the doping ratio is 5%, the degradation rate of LOMH increases from 55.45% to 63.06% compared with pure CNT material. 60 The results show that the CNTs have a higher binding capacity than the CNTs. 60 / CNT composites have good photocatalytic performance and are optimal when the ratio is 5%.

[0048] To further enhance the degradation effect of the catalyst, 1 mL 2 mmol / L PS (potassium persulfate) was added as an auxiliary agent to the C 60 / CNT composites were used to photocatalytically degrade LOMH. The experiment showed that the degradation effect was improved after adding PS, and the degradation rate of LOMH by CC5 composites increased to 93% at 60 min.

[0049] It should be noted that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present invention are all included in the technical scope of the present invention. In addition, without departing from the scope of the main purpose of the present invention, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present invention.

Claims

1. A C 60 / CNT composite photocatalytic material, characterized in that Including C 60 and carbon nanotubes; the C 60 The mass ratio of C to carbon nanotubes is 0.002-0.1; 60 Coated on the surface of carbon nanotubes and / or the C 60 Doped in the gaps between carbon nanotubes.

2. A C according to claim 1 60 / CNT composite photocatalytic material, characterized in that The C 60 The mass ratio to carbon nanotubes is 0.002~0.

05.

3. A C as claimed in claim 1 or 2 60 A method for preparing a CNT composite photocatalytic material, characterized in that: The following steps are involved: CNT materials and C 60 The material is placed in a solvent, mixed and then subjected to ultrasonic treatment, followed by centrifugal separation, and the separated product is dried and ground to obtain C 60 / CNT composites.

4. A C according to claim 3 60 A method for preparing a CNT composite photocatalytic material, characterized in that: The solvents include water and anhydrous ethanol.

5. A C according to claim 3 60 A method for preparing a CNT composite photocatalytic material, characterized in that: The ultrasonic treatment time is 1-2 hours; the drying temperature is 80-90° C., and the drying time is 5-8 hours.

6. A C as claimed in claim 1 or 2 60 Application of / CNT composite photocatalytic material in adsorption and degradation of lomefloxacin hydrochloride, characterized in that: The C 60 The mass ratio of / CNT composite photocatalytic material to lomefloxacin hydrochloride before degradation is 0.8~1.2:

1.

7. The use according to claim 6, characterized in that: The C 60 C / CNT composite photocatalytic material 60 The mass ratio to carbon nanotubes is 0.

002.

8. A C as claimed in claim 1 or 2 60 Application of / CNT composite photocatalytic material in photocatalytic degradation of lomefloxacin hydrochloride, characterized in that: The C 60 The mass ratio of / CNT composite photocatalytic material to lomefloxacin hydrochloride before degradation is 0.8~1.2:

1.

9. The use according to claim 8, characterized in that: The C 60 C / CNT composite photocatalytic material 60 The mass ratio of carbon nanotubes is 0.

05.

10. The use according to claim 8, characterized in that: The light source used in the photocatalytic degradation of lomefloxacin hydrochloride includes an LED light source; and potassium persulfate is added as an auxiliary agent in the photocatalytic degradation of lomefloxacin hydrochloride.